2012
DOI: 10.1080/00380768.2012.742002
|View full text |Cite
|
Sign up to set email alerts
|

Extractability of manganese and iron oxides in typical Japanese soils by 0.5 mol L−1hydroxylamine hydrochloride (pH 1.5)

Abstract: We investigated the extractability of manganese (Mn) and iron (Fe) oxides from typical Japanese soils (Entisols, Inceptisols, and Andisols) by 0.5 mol L À1 hydroxylamine hydrochloride (NH 2 OH-HCl) extraction (pH 1.5; 16 h shaking at 25 C; soil:solution ratio 1:40), referred as to HH mBCR , which is Step 2 (used for the reducible fraction) of the modified BCR (Community Bureau of Reference) sequential extraction procedure. The HH mBCR procedure extracted almost all Mn oxides from the non-Andisol samples, but f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…The results for the nonallophanic Andisol samples indicate that substantial amounts of Al were extracted from the Al-humus complex, although this extraction has been carried out before organically bound heavy metals are extracted in the modified BCR SEP. In contrast, HH mBCR extracted very small amounts of Fe from the Andisol samples, resulting in remarkably high Al/Fe ratios in these samples, being consistent with the results of Suda et al (2012). Oxa-Asc extracted large amounts of Fe except for the allophanic Andisol samples.…”
Section: Relationships Between Extractability Of Mn and Fe And Nh 2 Osupporting
confidence: 84%
See 2 more Smart Citations
“…The results for the nonallophanic Andisol samples indicate that substantial amounts of Al were extracted from the Al-humus complex, although this extraction has been carried out before organically bound heavy metals are extracted in the modified BCR SEP. In contrast, HH mBCR extracted very small amounts of Fe from the Andisol samples, resulting in remarkably high Al/Fe ratios in these samples, being consistent with the results of Suda et al (2012). Oxa-Asc extracted large amounts of Fe except for the allophanic Andisol samples.…”
Section: Relationships Between Extractability Of Mn and Fe And Nh 2 Osupporting
confidence: 84%
“…A common method is extraction with acidified 0.5 mol L -1 hydroxylamine hydrochloride (NH 2 OH-HCl), the second-step fraction in the modified Community Bureau of Reference (BCR) sequential extraction procedure (SEP) (Sahuquillo et al 1999). However, Suda et al (2012) reported that this method was not suitable for Japanese Andisols, especially allophanic Andisols, which showed poor extraction selectivity and low rates of extraction of short-range-ordered Fe oxides such as ferrihydrite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to XAS results, the residual fraction of SH_Dec2014 may be ascribed to aluminosilicates and iron oxy(hydr)oxides, whereas the AST_E45 residue is attributable to spinel-type non-reducible iron oxides. In fact, well-crystalline (e.g., hematite and goethite) and short-range-ordered (e.g., ferrihydrite) iron oxides could be not completely extracted by hydroxylamine hydrochloride -depending on the sample type, the sample mass/solution volume ratio, and the reagent concentration [52,53] and hence remain in the residual fraction.…”
Section: Leaching Tests Resultsmentioning
confidence: 99%
“…This percentage is much lower than what reported by Formenti et al [20], who observed the iron oxides contribution in Saharan dust being in the range 38-72%, and apparently not in accordance with XAS results, which point towards the presence of Fe(III) oxides in determining the observed spectral features. However, it has to be considered that some iron oxides identified in Saharan dust by XAS speciation analyses (e.g., hematite, goethite, ferrihydrite) could not be completely extracted in step II, hence contributing to the residual insoluble fraction ( [33]; [34]; [35]), which accounts for about 70% for all the Saharan dust samples considered in this study.…”
Section: Iron Speciation In the Different Advectionsmentioning
confidence: 99%